EDUKASI PENCEGAHAN ANEMIA PADA REMAJA DAN CARA MENANGGULANGINYA - Yona Harianti Putri; Delia Komala Sari; Rizki Oktarini; Hartadi, Ridwan; Lugastiningsih, Qori; Arisika; Khallissah Iz’zzah Aimar; Lia Ikhwan, Hikmah; Fatrisia Ananda, Liza; Salsabilah, Aliya (Andromeda: Jurnal Pengabdian Masyarakat Rafflesia, 2025)
Community service activities entitled "Education on Prevention of Anemia in Adolescents and How to Overcome It at Madrasah Aliyah Pancasila" aims to improve students' understanding of anemia, including its causes, symptoms, impacts, and prevention and management steps. Anemia, especially iron deficiency anemia, is a common health problem in adolescents, especially adolescent girls, which is often caused by unhealthy diets and low awareness of the importance of iron intake. The impacts include decreased concentration in learning, fatigue, and the potential for long-term health problems. Therefore, early education is very important to increase awareness and form healthy living behaviors. This activity is carried out through interactive counseling methods, distribution of educational brochures, screening of short videos, and discussion and evaluation sessions to measure the effectiveness of participants' understanding. The material presented includes the importance of consuming nutritious foods, sources of iron, the benefits of blood-boosting tablets, and the importance of routine health checks. It is hoped that through this activity, students will be able to understand and apply steps to prevent and overcome anemia independently, so that a sustainable healthy lifestyle is formed in everyday life. Keywords: Anemia, Adolescents, Nutrition Education, Iron, Madrasah